Venomous Loxosceles Species (Araneae, Haplogynae, Sicariidae) from Brazil: 2nâ™ = 23 and X1X2Y Sex Chromosome System as Shared Characteristics - Araujo, Douglas; Schneider, Marielle Cristina; Zacaro, Adilson Ariza; De Oliveira, Edson Gabriel [UNESP]; Martins, Rosana; Brescovit, Antonio Domingos; Knysak, Irene; Cella, Doralice Maria (Zoological Society of Japan, 2020)
The family Sicariidae comprises the genera Hexophthalma, Sicarius and Loxosceles. This latter is subdivided in eight monophyletic groups based on genitalia morphology and molecular analyses: amazonica, gaucho, laeta, and spadicea (South America); reclusa (North America); rufescens (Mediterranean); spinulosa and vonwredei (Africa). In Brazil, the genus Loxosceles is represented by 50 species. The mitotic and meiotic characteristics of eight Loxosceles species were analyzed in order to discuss the chromosome evolution, as well as the correspondence between cytogenetic data and morphological/molecular data for the delimitation of the South American groups of species belonging to this genus. All species studied in this work showed 2nâ™ = 23, including a X1X2Y sex chromosome system (SCS). Despite the similarity of diploid number and SCS, the species studied here differed regarding the chromosome morphology of some autosomal pairs, presence of secondary constrictions, size of X chromosomes and localization of Ag-NOR/rDNA sites. Based on all these chromosomal data, we verified a close relationship between Loxosceles species belonging to the amazonica and gaucho groups. Transmission electron microscopy (TEM) analysis of spread pachytene cells of L. gaucho showed regular synapsis between homologous autosomal chromosomes, but asynaptic behavior of the sex chromosomes. The axial elements of the sex chromosomes undergo conspicuous morphological modifications resulting in shortening of their length.
Keywords: brown spider; chromosome evolution; fluorescence in situ hybridization; meiosis; synaptonemal complex